CARBOHYDRATE METABOLISM AND IMMUNE-INFLAMMATORY INTERACTIONS IN DELAYED FRACTURE HEALING AFTER COVID-19 - Badriddinov Akobir Sadriddinovich; Khamdamov Bakhtiyor Zaripovich (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation Metabolic disorders such as insulin resistance and hyperglycemia have become increasingly common in post-COVID patients. These alterations are known to influence immune function and inflammation, both of which are critical in bone tissue repair. Analyzing how carbohydrate metabolism affects immune markers can improve diagnostic and therapeutic approaches for delayed consolidation. This article provides scientific research information about carbohydrate metabolism and immune-inflammatory interactions in delayed fracture healing after COVID-19.